Application of micro/nanorobot in medicine - Sun, Tianhao; Chen, Jingyu; Zhang, Jiayang; Zhao, Zhihong; Zhao, Yiming; Sun, Jingxue; Chang, Hao (Frontiers in Bioengineering and Biotechnology, 2024)
The development of micro/nanorobots and their application in medical treatment holds the promise of revolutionizing disease diagnosis and treatment. In comparison to conventional diagnostic and treatment methods, micro/nanorobots exhibit immense potential due to their small size and the ability to penetrate deep tissues. However, the transition of this technology from the laboratory to clinical applications presents significant challenges. This paper provides a comprehensive review of the research progress in micro/nanorobotics, encompassing biosensors, diagnostics, targeted drug delivery, and minimally invasive surgery. It also addresses the key issues and challenges facing this technology. The fusion of micro/nanorobots with medical treatments is poised to have a profound impact on the future of medicine.